Brown Seaweed Fucoidan in Cancer: Implications in Metastasis and Drug Resistance - María Elena Reyes; Ismael Riquelme; Tomás Salvo; Louise Zanella; Pablo Letelier; Priscilla Brebi (Marine Drugs, 2020)
Fucoidans are sulphated polysaccharides that can be obtained from brown seaweed and marine invertebrates. They have anti-cancer properties, through their targeting of several signaling pathways and molecular mechanisms within malignant cells. This review describes the chemical structure diversity of fucoidans and their similarity with other molecules such as glycosaminoglycan, which enable them to participation in diverse biological processes. Furthermore, this review summarizes their influence on the development of metastasis and drug resistance, which are the main obstacles to cure cancer. Finally, this article discusses how fucoidans have been used in clinical trials to evaluate their potential synergy with other anti-cancer therapies.